STRATEGI PENINGKATAN INVESTASI SEKTORAL DI KABUPATEN BIMA - Fajrin Hardinandar; Fitroh Auliani; Syafruddin Syafruddin; Rizky Amelia; Muhammad Akbar (Jurnal PenKoMi : Kajian Pendidikan dan Ekonomi, 2024)
One of the issues addressed in the 2021-2024 Regional Medium-Term Development Plan (RPJMD) of Bima District is the lack of promotion and coordination efforts for local investment, which has resulted in low investment levels. The aim of this study is to elaborate on the strategies that should be implemented to enhance cross-sectoral investments classified into four categories: agriculture, tourism, industry, and mining. By employing EFAS and IFAS analyses, our study findings conclude that collaboration, coordination, sustainable maintenance, and solid academic research are necessary to boost investments in these four sectors. Policy recommendations for investment enhancement include strengthening the agricultural sector, tourism, industrial zones, and mining through support for farmer groups, collaboration with universities, infrastructure development, access to agricultural business credit through regulations, academic manuscripts, and integrated tourism area development, as well as investment cooperation with stakeholders.